Effective writing ; improving scientific, technical and business communication - Turk, Christopher; Kirkman, John. (London : New York : Spon Press, 2003)
Effective communication is vital to science, engineering and business management. This thoroughly updated second edition with a new chapter on the use of computers and word-processors gives clear, practical advice illustrated with real-life examples on how to select, organize and present information in reports, papers and other documents.
Includes index.
Keywords: Technical writing; Writing Communication